KINETIC AND THERMODYNAMIC OF FREE AND IMMOBILIZED PROTEASE FROM ADULT HERMETIA ILLUCENS - ANNISA RAHMASARI KANTO - NIM: 20516012, DHINI
Hermetia illucens is a fly which has ability to decomposes organic waste. This ability comes from the digestive enzymes contained in its body. One of those enzymes is protease. In order to make such protease can be used in various applications, its kinetic and thermodynamic should be analyzed. Another unique feature from this fly is chitin and chitosan (chitin derived compound) content which are natural polymer that widely used as material support in enzyme immobilization. In this study, protease was isolated from adult H. illucens. The protease was fractionated and dialyzed. Then its molecular weight, protein content and specific activity were being determined. Chitin from adult H. illucens was isolated and deacetylated for making chitosan that will be used for protease immobilization. Then, kinetic and thermodynamic of free and immobilized protease were analyzed. Protease from partial purification in 60%-80% amonium sulfate fraction had the highest specific activity (449.32 U/mg). Its purity and molecular weight were then analyzed using SDS-PAGE and zymography. Zymogram showed active protease has molecular weight about 50 kDa. Chitin from adult H. illucens has been isolated as much as 17.93% of the total samples weight. Chitin was then deacetylated in oreder to convert it into chitosan by which the deacetylation reached about 74.74%. Protease was immobilized into chitosan by crosslinking method using glutaraldehyde as the crosslinker and it was 88.36% of protease successfully immobilized by this method. Specific activity of the immobilized protease was about 92.2% of free protease. The optimum pH and temperature of free protease as determined by response surface method (RSM) were about 7.8 and 47.9oC, respectively, while those of immobilized protease were found at pH 7.5 and 44.7oC. The effect of immobilization towards enzyme kinetic parameters was also evaluated. Kinetic parameters of Vmaxapp, Kmapp, kcatapp and kcatapp/Kmapp for free protease were about 344.1 U/mg, 4.387 mM, 286.7 s-1, and 78.44 s-1/mM, respectively, and were about 256.4 U/mg, 1.507 mM, 213.3 s-1, and 170.1 s-1/mM for the immobilized one, respectively. The immobilization also significantly prolong the enzyme working activity as indicated by the longer activity half-life, which was about 10.35 h for the free protease to 63.01 h for the immobilized one. The longer half-life of the immobilized protease was reflected by the lower value of its deactivation rate constant (kD) at 25oC which was about 0.011 h-1 compare to that of the free protease that was about 0.067 h-1. The slower deactivation rate of the immobilized protease was due to the higher potential barrier toward the activation state as reflected by enthalpy of deactivation ( ) that was more endothermic (+7.68 kkal/mol) than that of the free protease (+1.12 kkal/mol). This study, thus showed that chitosan-immobilized protease from adult H. illucens exhibited better catalytic performance and stability than the unimmobilized one.